2014
DOI: 10.5152/tjg.2014.5454
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of insulin-like growth factor II mRNA-binding protein 3 (IMP3) as a new marker for the diagnosis of esophageal adenocarcinoma in challenging cases

Abstract: Background/Aims: Insulin-like growth factor II mRNA-binding protein 3 (IMP3) is an oncofetal protein with vital function during human embryogenesis in terms of cellular growth and migration. Although it has minimum and undetectable expression in human adult tissues, it is highly expressed in various types of cancer. Few studies have recommend application of IMP3 expression to diagnose challenging cases of esophageal adenocarcinoma. This survey was aimed to evaluate the benefit of IMP3 expression detection in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The overexpression of IGF2BP3 may therefore be a supplement to the diagnosis of HGIN, especially in challenging cases. 15 Overall, our results suggest a potential tissue marker for the diagnosis of HGIN and provide a complementary strategy to histopathologic examination. A large sample will be enrolled for further test validation.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The overexpression of IGF2BP3 may therefore be a supplement to the diagnosis of HGIN, especially in challenging cases. 15 Overall, our results suggest a potential tissue marker for the diagnosis of HGIN and provide a complementary strategy to histopathologic examination. A large sample will be enrolled for further test validation.…”
Section: Discussionmentioning
confidence: 68%
“…The positive rate of IGF2BP3 in squamous cell carcinoma of the skin, 16 the head and neck, 1 , 17 and the tongue 18 were 57%, 61%, and 77%, respectively. According to the study by Kazeminezhad et al, 15 the positive rate of IGF2BP3 was about 91% in advanced esophageal adenocarcinoma. In the study by Yantiss et al, 21 IGF2BP3 was with a 97% positive rate in pancreatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some other studies have reported higher expression of hnRNP‐B1 (Matsuyama et al, ) and ‐H1 (Sun, Liu, Liu, & Zhao, ), NF45 (Ni et al, ), insulin‐like growth factor 2 mRNA‐binding protein (IGF2BP)‐2 (Barghash, Golob‐Schwarzl, Helms, Haybaeck, & Kessler, ) and ‐3 (W. Feng et al, ; Kazeminezhad, Mirafsharieh, Dinyari, Azizi, & Ebrahimi, ; Trivedi, Cartun, & Ligato, ), DEAD‐Box Helicase 46 (B. Li, Li, et al, ), and Musashi‐1 (Mokrowiecka et al, ) in EC tissues. Because enhanced expression of these molecules was correlated with poor pathologic features and worse survival of patients, they are thought to be useful as new prognostic markers and potential anticancer targets in EC.…”
Section: Major Functions Of Rbps In Gi Cancermentioning
confidence: 97%
“…While, recent evidence associates derailed expression or activity of these RBPs with several genetic diseases including cancer, their cellular target repertoire, how they regulate the transcriptome and proteome and whether they can be used for therapeutic intervention warrants further investigation [811]. IMP3 is an example of an oncofetal RNA binding protein, which has been associated with various malignancies [1216]. Few of the bonafide targets of the protein are emerging from the recent research [9].…”
Section: Introductionmentioning
confidence: 99%